DIGESTIBILITY OF DRY AND ORGANIC MATTER AND METABOLITE PRODUCTS FROM BROILER LITTER FERMENTED BY DIFFERENT INOCULANS - I G., Wyasaputra; Miwada, I N. S.; Mudita, I M. (Jurnal Peternakan Tropika; Vol 11 No 3 (2023): Vol. 11 No. 3 Tahun 2023; September - December, 2023)
This study aimed to determine the effect of different types of inoculant fermentation in broiler litter fermentation on dry matter and organic matter digestibility, and metabolite products and to determine the inoculants that produced the highest dry matter and organic matter digestibility and metabolite products among Yeast, EM4 and Bio-BaliTani.  The study used a completely randomized design (CRD) consisting of 4 treatments, namely litter without fermentation (LF0), EM4 inoculants ( Effective Microorganism 4) (LF1), yeast inoculants ( Saccharomyces cerevisiae ) (LF2), and Bio-BaliTani inoculans (LF3). Each treatment used 4 replications.  The variables observed were dry matter and organic matter digestibility (KcBK and KcBO) in vitro and rumen fermentation products (pH, VFA, and N-NH 3 ).  The results showed that the use of yeast inoculants (LF2) was able to produce KcBK of 62.63% (P<0.05) compared to LF0.  The Bio-BaliTani (LF3) inoculant treatment resulted in the highest KcBO of 65.17% (P<0.05) compared to LF0.  The Bio-BaliTani (LF3) inoculant treatment resulted in the lowest pH of 6.54 (P<0.05) compared to LF0. The use of yeast inoculants resulted in the highest VFA of 141.96 mM (P<0.05) compared to LF0. The use of Bio-Balitani inoculants resulted in the highest N-NH 3 concentration of 8.31 mM (P<0.05) compared to LF0.  Based on the results of the study, it can be concluded that the use of various types of inoculants in the fermentation process of broiler litter can increase the digestibility of dry matter and organic matter (KcBK and KcBO) and metabolite products (VFA, N-NH 3 , and acidity) of broiler litter in vitro.  Fermentation of broiler litter using Yeast inoculants produced the highest KcBK and VFA values, while broiler litter fermentation using Bio-BaliTani inoculants produced KcBO, N-NH 3 , and the highest acidity. Keywords: Poultry litter, inoculants, digestibility, rumen fermentation products